From Subject to Object: Preservation and awareness of the vulnerable Cape Gannet - Oettle, Tilanie (School of Architecture, Planning and Geomatics, 2023)
This dissertation investigates and describes the concept of how an Ecocentric world model is possible by using architecture as a tool to achieve this. The relationship between humans and nature should be further investigated and developed as there is a current disconnect between these two. As a result, the natural environment is degrading, ecosystems are becoming dysfunctional and species extinction is increasing. The Cape Gannet forms a critical element in the dissertation as there is a need to address the decrease in its population, especially on Malgas Island (located close to the site). The design seeks to engage with this subject and find possible solutions as to how this issue can be addressed in Saldanha Bay, South Africa. The design draws individuals to the site, which is in close proximity to the island, to engage with these species, providing awareness and an educational basis regarding the species as well as the natural environment of the area. At the same time, the design seeks to enhance the existing landscape by making a positive impact. The research topic also identifies ways in which architecture could engage with its surroundings through a multi-species cohabitation approach which could alleviate ongoing biodiversity losses in an Anthropocentric world model. By incorporating stabilization and research facilities focused on the Cape Gannet, research and monitoring facilities focused on the ocean, as well as awareness and educational spaces, the design starts to form a basis to reverse the effects of the possible extinction of these species in the future, address the health of the ocean and provides solutions to how humans, the natural environment and animals can co-exist amongst each other in a symbiotic manner.